Development of an electroporation method and expression patterns of bacteriocin-encoding genes in Companilactobacillus crustorum MN047. (December 2021) - Wang, Panpan; Wang, Tao; Ismael, Mohamedelfateih; Wang, Xin; Yi, Yanglei; Lü, Xin
Abstract: Companilactobacillus crustorum MN047 isolated from koumiss possesses excellent inhibition activity against Gram-positive and Gram-negative bacteria, which is attributed to its multiple novel bacteriocin production. However, this species has not been applied in food industry due to unclear production patterns of multiple bacteriocins. The green fluorescent protein ( gfp ) based promoter-trap reporter system is conducive to explore the expression patterns of certain genes in bacteria. However, the application of such a system in C. crustorum is hampered by low electroporation efficiency. Thus, various parameters that may influence the electroporation efficiency were progressively optimized, a high electroporation efficiency of up to 10 5  CFU/μg DNA in C. crustorum was obtained. Taking the advantage of the high transformation efficiency, the expression patterns of ten bacteriocin-encoding genes in C. crustorum MN047 were investigated by a GFP-based promoter-trap system. The intensity of fluorescence of transformed cells was measured under various growth conditions and enhanced bacteriocin production was achieved. Finally, the crude culture of C. crustorum MN047 under optimal growth condition was proved to be more effective to inhibit the pollution of Escherichia coli and Staphylococcus aureus in pork preservation. This study provides a novel strategy to explore the production pattern of bacteriocin and proves the food preservation potential of C. crustorum . Highlights: The electroporation efficiency of C. crustorum was improved to 5.2 × 10 5  CFU/μg DNA. Four bacteriocins were screened to contribute greatly to antibacterial activity of C. crustorum. A promoter-GFP reporting system was used to improve bacteriocin production of C. crustorum. The bacteriocin expression of C. crustorum increased in weak acid MRS broth with 0.1 M sucrose at 37 °C. Crude culture of C. crustorum showed promising food preservation potential after optimization.